Realization of Negative Group Delay Network Using Defected Microstrip Structure - Girdhari Chaudhary; Yongchae Jeong; Jongsik Lim (International Journal of Antennas and Propagation)
A design of negative group delay (NGD) networks using a U-shaped defected microstrip structure (DMS) and lumped elements is presented in this paper. The signal attenuation characteristics of DMS were utilized to get NGD time. The group delay (GD) time and signal attenuation of the proposed networks are controlled by an external resistor connected across the DMS slot. For experimental validation, a single-stage and cascaded two-stage NGD networks were designed and fabricated. From experimental results, the GD of -8.24±1.1 ns with the maximum insertion loss of 37.84 dB was obtained over bandwidth of 40 MHz.